Exploring the Impact of Online Games on Learning Motivation in Primary Students: A Strong Negative Correlation: Menjelajahi Dampak Permainan Daring terhadap Motivasi Belajar pada Siswa Sekolah Dasar: Korelasi Negatif Kuat - A’yun, Qurrota; Tirtoni, Feri (Indonesian Journal of Education Methods Development, 2023)
This quantitative correlational study investigates the relationship between online games and learning motivation among fifth-grade students at an elementary school. Employing questionnaires and interviews, the study analyzed data from 27 students using descriptive analysis and the product moment correlation test. The results revealed that online game engagement exhibited a high level (66.67%) within the 61-80% range, while learning motivation demonstrated a medium level (66.67%) within the 41-60% range. Utilizing SPSS version 26, the Pearson correlation value of -0.713 indicated a significant (p < 0.05) strong negative correlation between online games and learning motivation. This suggests that as online game involvement increases, learning motivation tends to decrease in this student population. These findings emphasize the need for educational strategies that balance the use of online games to foster intrinsic motivation and effective learning outcomes. Highlights: Correlation Between Online Games and Learning Motivation: This study examines the connection between online games and learning motivation in fifth-grade students, revealing a strong negative correlation. Data Analysis Techniques: Utilizing questionnaires and interviews, the research employs descriptive analysis and correlation tests to assess the relationship between online game engagement and learning motivation. Implications for Education: The results underscore the importance of balanced educational strategies that leverage online games to enhance intrinsic motivation and optimize learning outcomes in students. Keywords: Online games, learning motivation, elementary school, correlational study, student population.